2022
DOI: 10.3390/cells11244033
|View full text |Cite
|
Sign up to set email alerts
|

Age, Education Years, and Biochemical Factors Are Associated with Selective Neuronal Changes in the Elderly Hippocampus

Abstract: Brain aging involves regional alterations of specific cellular subpopulations in the human hippocampus: a network hub for memory consolidation. The present study investigates whether age, sex, education years, and the concentration of neuropathological and inflammatory proteins influence neuronal-type marker expression in the elderly hippocampus. We analyzed the digital images (1 µm/pixel) of postmortem hippocampal sections from 19 non-demented individuals (from 78 to 99 years). This material was obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Interestingly, hippocampus FC appeared to increase in late ages, which also seemed to occur with the expression of some hippocampal cell markers. On the one hand, it has been shown that brain aging involved regional alterations of specific cellular subpopulations in the human hippocampus [ 62 , 63 ]. For example, increased glutamatergic transporter was observed in multiple hippocampal subfields at late ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, hippocampus FC appeared to increase in late ages, which also seemed to occur with the expression of some hippocampal cell markers. On the one hand, it has been shown that brain aging involved regional alterations of specific cellular subpopulations in the human hippocampus [ 62 , 63 ]. For example, increased glutamatergic transporter was observed in multiple hippocampal subfields at late ages.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased glutamatergic transporter was observed in multiple hippocampal subfields at late ages. This glutamatergic marker was positively correlated with beta-amyloid and tau proteins [ 63 ]. The GA1 hippocampal area was also positively correlated with the concentrations of interferon-gamma and brain-derived neurotrophic factor (BDNF).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, IL-7 has been associated with dysregulated energy metabolism, leading to malnutrition in cancer patients [ 86 ]. There is also evidence that IL-7 may affect the mental state of cancer patients by influencing neurotransmitter levels, leading to psychological problems such as anxiety and depression, further reducing the patient’s quality of life [ 87 ].…”
Section: Il-7 In Tumour Therapymentioning
confidence: 99%